Poster 252: Revision Risk of Hamstring Versus Hybrid Graft in Anterior Cruciate Ligament Reconstruction. Issue 7 (30th July 2022) - Chang, Richard; Royse, Kathryn; Burfeind, William; Prentice, Heather; Maletis, Gregory; Mirzayan, Raffy
Objectives: Hamstring autograft (HA) is a commonly used graft for anterior cruciate ligament reconstruction (ACLR). Hamstring tendon harvest can occasionally result in a small diameter graft, leaving the surgeon with several options. One option is to augment the hamstring graft with allograft tendon to increase the combined graft diameter forming a hybrid graft (HG). Inconsistent results of HG reconstructions have been reported, with some studies reporting worse outcomes for HG while others showing no difference between the two types of grafts. However, these studies have small sample sizes or are of an older patient population. The purpose of our study was to compare the revision rates of HA versus HG grafts in a young patient population. Methods: We conducted a retrospective cohort study of prospectively collected data from our integrated healthcare system's ACLR Registry. Patients< 25 years of age with a primary, isolated ACLR performed between 2005-2020 were identified; those with prior surgery in the index knee, double bundle, and infections (septic revisions) were excluded. The exposure of interest was graft type and diameter size, including <8mm HA and> 8mm HG. Hybrid graft was defined as a hamstring tendon augmented with an allograft tendon to increase the graft diameter. Grafts with unknown diameter sizes and other graft types were excluded. A secondary analysis examined 7mm and 7.5mm HA vs> 8mm HG. Propensity score-weighted Cox proportional hazard regression was used to evaluate the risk of aseptic revision during follow-up. Propensity score weights were calculated prior to evaluation of the outcome using multivariable logistic regression analysis and included age, sex, body mass index, race/ethnicity, femoral fixation, tibial fixation, femoral tunnel method, and activity at injury. Hazard ratios (HR) and 95% confidence intervals (CI) are presented. A P<0.05 was considered statistically significant. Results: The final cohort comprised 1, 945 ACLR (548 were> 8mm HG and 1397 were <8mm HA, including 651 with 7mm diameters and 672 with 7.5mm). At 8-years follow-up, the crude cumulative aseptic revision probability for> 8mm HG was 9.1%, while <8mm HA was 10.9% (Figure 1 ); corresponding cumulative probabilities for 7mm and 7.5mm HA were 11.1% and 11.2% respectively. After adjustment with propensity score weighting, we failed to observe a difference in aseptic revision risk for <8mm HA compared with> 8mm HG (HR=1.15, 95% CI = 0.72-1.82, p=0.56) (Table 1 ). Similarly, no difference was observed for 7mm HA (HR= 1.23, 95% CI=0.71-2.11, p=0.46) and 7.5mm HA (HR=1.16, 95% CI =0.74-1.82, p=0.52) compared to HG. Conclusions: In our cohort study of 1, 945 patients, we failed to detect a statistical difference in the risk of aseptic revision between a HA < 8mm and a HG> 8mm. The clinical significance is that augmentation of HA with an allograft does not appear to decrease the risk of aseptic revision and may not be necessary. Future studies should be conducted to confirm these findings. Figure 1. Cumulative Incidence of Aseptic Revision by Graft Type/Diameter Size. Table 1. Crude Cumulative Revision Probability And Adjusted Risk After Aclr By Graft Type/Diameter Size.